Integrated management of climate and urban policies:: a proposal for legal evaluation in municipalities of the Metropolitan Region of São Paulo - Campos, Paula Prado; Philippi Junior, Arlindo; Santana, Paula (Sustainability in Debate, 2015)
Climate change planning and public policy management require the action of different actors, all mediated by the State, as well as the adoption of adaptation and mitigation strategies and policies that involve different sectors and affect the use, occupation and transformation of urban land. Admitting the importance of the legislation as a structuring element of the implementation process of public policies, legal norms regarding to Urban Policies and Climate Change of some counties of the Metropolitan Region of São Paulo were evaluated. This article describes the methodological process of the development of an analysis tool from the listing of theoretical categories. The method has highlighted the fragility of the metropolitan side and showed that although the structuring of the integrated management is legally supported, the achievement of this administration will be reached with the effective progress in the organization of regional structures of planning and with public policy management under the spatial planning logic.